Endoscopy-guided, renal-sparing sclerotherapy in 2 dogs with idiopathic renal hematuria - De Schrijver, Rebecca; De Swert, Joris; Fortrie, Ruth; Van Klaveren, Nicolien (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2025)
A 10-month-old male Australian Shepherd and a 3.5-year-old female Staffordshire Bull Terrier were presented due to chronic gross hematuria. Further diagnostics, including ultrasonography and cystoscopy of the urinary tract, revealed no cause for the bleeding. Accordingly, a diagnosis of unilateral idiopathic renal hematuria (IRH) was made.Treatment with Yunnan Baiyao was unsuccessful. Both patients underwent retrograde ureteropyelography and unilateral sclerotherapy. A 5% povidone iodine mixture and a 0.5% silver nitrate solution were administered sequentially into the renal pelvis multiple times and left there for 20 minutes. The second dog showed a tortuous course of the ureter caused by bilateral ectopic ureters, already treated with a laser ablation. This made treatment considerably more challenging. Giving the persistence of hematuria, the procedure was repeated 3 weeks later. Neither dog exhibited any complications associated with the treatment and they remain free of microscopic hematuria 15 and 11 months later, respectively.The reported cases demonstrate that sclerotherapy should be considered as a renal-sparing therapy, even in dogs with more complicated conditions.
Keywords: Minimally invasive; fluoroscopic; ureteropyelogram; silver nitrate; povidone iodine; urethrocystoscopy